The impact of tibolone on cardiovascular system and haemostasis of menopausal women - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Tibolone – a synthetic steroid with oestrogen, progesterone and androgen activity – influences circulatory system and haemostasis of menopausal women. Its impact on lipid profile, inflammatory parameters, coagulation, fibrinolysis and vascular wall can modify the risk of ischemic heart disease, stroke and deep vein thrombosis. Available date testify clearly that tibolone is a good alternative to oestrogen-progesterone menopausal hormone therapy (MHT).